Kinetoplastid-specific X2-family kinesins interact with a kinesin-like pleckstrin homology domain protein that localizes to the trypanosomal microtubule quartet - Benz, Corinna; Müller, Nora; Kaltenbrunner, Sabine; Váchová, Hana; Vancová, Marie; Lukeš, Julius; Varga, Vladimír; Hashimi, Hassan (Molecular microbiology, 2022)
Kinesins are motor proteins found in all eukaryotic lineages that move along microtubules to mediate cellular processes such as mitosis and intracellular transport. In trypanosomatids, the kinesin superfamily has undergone a prominent expansion, resulting in one of the most diverse kinesin repertoires that includes the two kinetoplastid-restricted families X1 and X2. Here, we characterize in Trypanosoma brucei TbKifX2A, an orphaned X2 kinesin. TbKifX2A tightly interacts with TbPH1, a kinesin-like protein with a likely inactive motor domain, a rarely reported occurrence. Both TbKifX2A and TbPH1 localize to the microtubule quartet (MtQ), a characteristic but poorly understood cytoskeletal structure that wraps around the flagellar pocket as it extends to the cell body anterior. The proximal proteome of TbPH1 revealed two other interacting proteins, the flagellar pocket protein FP45 and intriguingly another X2 kinesin, TbKifX2C. Simultaneous ablation of TbKifX2A/TbPH1 results in the depletion of FP45 and TbKifX2C and also an expansion of the flagellar pocket, among other morphological defects. TbKifX2A is the first motor protein to be localized to the MtQ. The observation that TbKifX2C also associates with the MtQ suggests that the X2 kinesin family may have co-evolved with the MtQ, both kinetoplastid-specific traits.
Keywords: Cytoskeleton; cytoskelet; PH-doména; Microtubules; morphogenesis; Pleckstrin Homology Domains; Kinesins; cytoskeleton; kinesin; Trypanosoma; microtubule quartet; microtubules; mikrotubuly; protozoální proteiny; Protozoan Proteins; Trypanosoma brucei brucei; kineziny